Closing-Wedge Distal Femoral Osteotomies—Retrospective Study - Cabral, Pedro Barreira (Sociedade Brasileira de Ortopedia e Traumatologia. Published by Thieme Revnter Publicações Ltda, 2019)

(untitled) (Rev Bras Ortop (Sao Paulo))
Objective  To describe the surgical technique of distal closing-wedge femoral osteotomy and a cases series submitted to this technique. Methods  A total of 26 patients submitted to medial closing-wedge distal femoral osteotomy from 2002 to 2013 were evaluated. All of the patients had their medical files and imaging exams reviewed to evaluate the degree of correction and their current state. Results  Out of the 26 patients, 12 were male and 14 were female. Their mean age was 47.15 years old. In all of the cases, a neutral alignment related to the anatomical axis was achieved. Most of the patients presented bone healing at 6 weeks. There were no cases of bleeding during the surgery. One patient presented with delayed bone healing. One patient complained of plaque-related discomfort, requiring the removal of the device. One patient had a superficial infection, but no osteotomy revision was needed. There were no cases of deep venous thrombosis or of pulmonary thromboembolism. To date, there has been no conversion to total knee replacement. Conclusion  Treatment with medial closing-wedge distal femoral osteotomy sustained the proposed correction in patients with up to 15 years of follow-up.